2020
DOI: 10.1038/s41598-020-63724-y
|View full text |Cite
|
Sign up to set email alerts
|

FIBTEM Improves the Sensitivity of Hyperfibrinolysis Detection in Severe Trauma Patients: A Retrospective Study Using Thromboelastometry

Abstract: Rotational thromboelastometry (ROTEM) can only detect high-degree hyperfibrinolysis (HF), despite being frequently used in trauma patients. We investigated whether considering FIBTEM HF (the presence of maximal lysis (ML) > 15%) could increase ROTEM-based HF detection's sensitivity. This observational cohort study was performed at a level 1 trauma centre. Trauma patients with an Injury Severity Score (ISS) > 15 who underwent ROTEM in the emergency department between 2016 and 2017 were included. EXTEM HF was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
0
23
1
1
Order By: Relevance
“…Hyperfibrinolysis as measured with viscoelastic testing is a relevant finding, associated with increased mortality and massive transfusion, with incidences reported as high as 32.5% based on FIBTEM lysis index at 60 minutes less than 85%. 7,37,38 In our cohort, hyperfibrinolysis measured by lysis index at 30 min is rare. This is not unexpected given the low sensitivity of lysis index at 30 min.…”
Section: Discussionmentioning
confidence: 83%
“…Hyperfibrinolysis as measured with viscoelastic testing is a relevant finding, associated with increased mortality and massive transfusion, with incidences reported as high as 32.5% based on FIBTEM lysis index at 60 minutes less than 85%. 7,37,38 In our cohort, hyperfibrinolysis measured by lysis index at 30 min is rare. This is not unexpected given the low sensitivity of lysis index at 30 min.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, looking at the FIBTEM curve for evidence of fibrinolysis, as plasmin cleaves fibrin, demonstrates further confirmation of true fibrinolysis. 38 The QStat FCS curve provided similar evidence of fibrinolysis.…”
Section: Discussionmentioning
confidence: 85%
“…Although, our study was limited to the analysis of extem and aptem, it should be remembered that some authors have shown that the other available tests for ROTEM, fibtem, in which the contribution of platelets to the formation of clots is inhibited by cytochalasin-D, may be used as a method of improving the sensitivity of hyperfibrinolysis detection in some clinical scenarios [17][18][19].…”
Section: Discussionmentioning
confidence: 99%